Design of a Low Voltage DC Mini-grid for Isolated Healthcare Centres - Dhinakaran, Vishnu; Akash, K.; Viswanathan, Rakshaa; Rakesh Kumar, A.; Arul Daniel, S. (Distributed Generation & Alternative Energy Journal, 2021)
Primary healthcare centres are essential to any inhabited place in the world. A lack of electrical power from the grid should not be a reason for people in remote rural areas to miss out on basic healthcare. In developing countries like India, rural healthcare centres usually have intermittent or no grid supply and run on diesel generator-based electricity or other conventional sources, if at all there are such centres established. This, however, contributes to environmental degradation and is also expensive to maintain, considering fluctuating fuel prices. To turn the dependence on renewable energy sources like photovoltaics would pave the way to sustainable energy production and utilization, which costs less in the long run. This research work aims at designing an islanded low voltage DC solar mini-grid that will provide enough power to sustain a primary healthcare centre that has less to no access to the national grid. Previous works in this context tend to rely on varying extents of intermittent supply from the national grid, which may not be the reality in most Indian rural areas. Additionally, an unreliable source of power from the grid which is also difficult to predict would make sensitive and important loads less accessible.